2022
DOI: 10.14202/vetworld.2022.1601-1609
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical and laboratory findings associated with feline immunodeficiency virus and feline leukemia virus infections in Bangkok, Thailand

Abstract: Background and Aim: Feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) are retroviruses associated with chronic and neoplastic diseases in domestic and non-domestic cats. There has been increasing interest in the clinical importance of feline retroviruses in Thailand and the identification of associated risk factors in domestic cats. To prevent the spread of retroviral diseases and improve the management of retrovirus-infected cats, risk factors and associated clinical laboratory data must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…Second, the median age of cats infected with FeLV was two years, similar to that reported in other studies [11,23,24]. However, there was no significant difference in the median age of uninfected cats, which is probably related to the high prevalence, around 70%, of young cats under 4 years old in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, the median age of cats infected with FeLV was two years, similar to that reported in other studies [11,23,24]. However, there was no significant difference in the median age of uninfected cats, which is probably related to the high prevalence, around 70%, of young cats under 4 years old in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Despite this, studies have shown that hematological disorders and lymphoma, the main neoplasia associated with FeLV, can also occur in non-productive infections [6,20,31,32]. Anemia is one of the most frequently described hematological disorders and clinical manifestations in FeLV-infected cats, as observed in the present study [6,13,24,33]. In addition, as reported by other studies, cats with anemia were more likely to be FeLV positive [24].…”
Section: Discussionsupporting
confidence: 70%
“…The most significant initiators of FIP infection in cat care facilities, shelters, and housing are feline retrovirus infections [7]. Infection with FeLV and FIV can cause multiple, variable, and clinical signs depending on the disease stage [3,8]. The most common outcomes of latent FeLV infection are immunosuppression, bone marrow suppression, and tumorigenesis (lymphoma), whereas FIV can lead to acquired immunodeficiency and an increased risk of opportunistic infections [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports regarding FIP, FeLV, and FIV viruses individually [8,14,20], but the differences between individual and coinfection have not been published to the best of our knowledge. This study aimed to investigate changes in the clinicopathological and laboratory parameters of FIP with and without retrovirus coinfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation